Medical waste incineration fly ash as an effective adsorbent for removing dyes from textile effluent and methylene blue from synthetic aqueous solutions - Tanvir Ahmed; Mir Tanvir Al Biruni; Simanta Azad; Mehedi Hasan (Case Studies in Chemical and Environmental Engineering, 2024)
This study explores the utilization of Medical Waste Incineration Fly Ash (MWIFA) as a cost-effective adsorbent for removing dye from textile wastewater and synthetic aqueous solutions. Various factors were investigated in batch experiments, yielding impressive dye removal efficiencies of up to 98%. Optimal conditions were determined at 7.5 g/L adsorbent dosage, 40-min contact time, and 200 rpm agitation speed. The Freundlich isotherm model demonstrated a better fit than the Langmuir model, while Lagergren's pseudo second-order kinetic model highlighted chemisorption dominance. Laboratory-scale experiments suggest that MWIFA has the potential to be a viable and cost-effective adsorbent for treating wastewater. However, careful evaluation of environmental impacts is essential for large-scale application.